2019
DOI: 10.1016/j.cjco.2019.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Low High-Sensitivity Troponin Thresholds Identify Low-Risk Patients With Chest Pain Unlikely to Benefit From Further Risk Stratification

Abstract: Background: Very low high-sensitivity cardiac troponin T (hs-cTnT) thresholds on presentation can rule out acute myocardial infarction (AMI), but the ability to identify patients at low risk of 30-day major adverse cardiac events (MACE) is less clear. This study examines the sensitivity of low concentrations of hs-cTnT on presentation to rule out 30-day MACE. Methods: This prospective cohort study enrolled patients with chest pain presenting to the emergency department with nonischemic electrocardiograms who u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
(33 reference statements)
0
7
0
Order By: Relevance
“…Very low levels of hsTnT are associated with reduced occurrence of 30-day MACE in patients presenting to the ED with chest pain. In one center, for patients presenting with chest pain and non-ischaemic ECG changes, a cut-off of hsTnT<5 ng/L taken at least 3 h from symptoms onset was able to rule out 30-day MACE (defined as AMI, revascularization, or cardiac death) (NPV 99.0%) [24] . Another study used a cut-off of 0- and 3-hour hsTnT ≤ 19 ng/L for 30-day MACE (NPV 99.3%), and found that lowering the cut-off to 6 ng/L did not increase the NPV [25] .…”
Section: Discussionmentioning
confidence: 99%
“…Very low levels of hsTnT are associated with reduced occurrence of 30-day MACE in patients presenting to the ED with chest pain. In one center, for patients presenting with chest pain and non-ischaemic ECG changes, a cut-off of hsTnT<5 ng/L taken at least 3 h from symptoms onset was able to rule out 30-day MACE (defined as AMI, revascularization, or cardiac death) (NPV 99.0%) [24] . Another study used a cut-off of 0- and 3-hour hsTnT ≤ 19 ng/L for 30-day MACE (NPV 99.3%), and found that lowering the cut-off to 6 ng/L did not increase the NPV [25] .…”
Section: Discussionmentioning
confidence: 99%
“…This study is a secondary analysis of data from a completed prospective cohort study that validated rapid diagnostic algorithms for myocardial infarction using high-sensitivity cardiac troponin-T [15,16] at a large urban level one trauma and regional percutaneous coronary intervention centre in Calgary, AB from August 2014 to September 2016. The detailed methods of the parent study are described elsewhere [15,16].…”
Section: Methodsmentioning
confidence: 99%
“…This study is a secondary analysis of data from a completed prospective cohort study that validated rapid diagnostic algorithms for myocardial infarction using high-sensitivity cardiac troponin-T [15,16] at a large urban level one trauma and regional percutaneous coronary intervention centre in Calgary, AB from August 2014 to September 2016. The detailed methods of the parent study are described elsewhere [15,16]. In brief, trained research assistants approached patients' attending ED physicians who prospectively collected clinical variables including symptoms, cardiovascular risk factors, medical history, physicians' assessment of the probability of acute coronary syndromes (low, moderate, high risk) and HEART score.…”
Section: Methodsmentioning
confidence: 99%
“…A total of 1,167 eligible patients with at least one hs-cTnT sample collected were enrolled as part of a related study examining hs-cTnT concentrations on presentation (0-hour), which has been published separately. 3 Of these, 559 patients were excluded because they did not require serial troponin sampling to rule out MI in the opinion of the attending emergency physician (usually because of prolonged and/or atypical symptoms), leaving 608 patients eligible for this study. The final data set included 350 patients with valid 1-hour and 550 patients with valid 2-hour hs-cTnT samples (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…1 Research has demonstrated that very low concentrations of high-sensitivity cardiac troponin (hs-cTn) sampled on ED arrival, especially in combination with a non-ischemic electrocardiogram (ECG), are highly sensitive for index myocardial infarction (MI). 2,3 However, guidelines recommend a single hs-cTn testing strategy only for patients with at least 3-hours since symptom onset given the risk of falsenegative results in early presenters. 4 Because the majority of patients will not meet these stringent criteria, serial hs-cTn sampling is recommended for most patients.…”
Section: Introductionmentioning
confidence: 99%